Emulating a target trial of antiretroviral therapy regimens started before conception and risk of adverse birth outcomes. (2nd January 2018) - Caniglia, Ellen C.; Zash, Rebecca; Jacobson, Denise L.; Diseko, Modiegi; Mayondi, Gloria; Lockman, Shahin; Chen, Jennifer Y.; Mmalane, Mompati; Makhema, Joseph; Hernán, Miguel A.; Shapiro, Roger L.
Abstract : Objective: To compare the effect of preconception initiation of zidovudine, lamivudine, nevirapine (ZDV/3TC/NVP) versus tenofovir, emtricitabine, efavirenz (TDF/FTC/EFV) on adverse birth outcomes. Design: Emulation of a hypothetical (target) trial using a birth surveillance study in Botswana during an era of CD4 + -based antiretroviral therapy (ART) initiation. Methods: In women who initiated ART less than 3 years from HIV diagnosis, conceived 0.5–5 years after ART initiation, and delivered at least 24-week gestation, we estimated risk ratios for stillbirth, preterm delivery (<37 weeks), very preterm delivery (<32 weeks), small-for-gestational-age (SGA) (<10 percentile), very SGA (<3 percentile), and any adverse or severe birth outcome for first-line ZDV/3TC/NVP versus TDF/FTC/EFV. We conducted a historical comparison in women who initiated TDF/FTC/EFV in 2012–2015 and ZDV/3TC/NVP in 2004–2011, and a contemporaneous comparison in an era of overlapping use from 2009 to 2013. Results: In the historical comparison, 1108 women initiated TDF/FTC/EFV and 637 initiated ZDV/3TC/NVP. In the contemporaneous comparison, 1052 initiated TDF/FTC/EFV and 298 initiated ZDV/3TC/NVP. TDF/FTC/EFV initiators were younger and more likely to be nulliparous than ZDV/3TC/NVP initiators in both comparisons. In the historical comparison, the adjusted risk ratios (95% confidence interval) comparing ZDV/3TC/NVP with TDF/FTC/EFV were 2.95 (1.76, 4.96) for stillbirth, 1.40 (1.17, 1.67) for preterm delivery, 2.58 (1.70, 3.91) for very preterm delivery, 1.96 (1.64, 2.34) for SGA, 2.32 (1.73, 3.09) for very SGA, 1.54 (1.38, 1.72) for any adverse birth outcome, and 2.20 (1.76, 2.75) for any severe birth outcome, and were similar in the contemporaneous comparison. Conclusion: Preconception initiation of ZDV/3TC/NVP compared with TDF/FTC/EFV may increase the risk of adverse birth outcomes. Abstract : Supplemental Digital Content is available in the text